The Impact of The Utilization of AI by Students In Arabic Language Learning at SMA Muhammadiyah 01 Taman: Dampak Pemanfaatan AI Oleh Siswa Dalam Pembelajaran Bahasa Arab Di SMA Muhammadiyah 01 Taman - Emirsyah Gibran Mustofa; Moch. Bahak Udin By Arifin (Academia Open, 2025)
General Background: The rapid development of Artificial Intelligence has transformed educational practices, including foreign language instruction in secondary schools. Specific Background: In Arabic language learning, AI tools such as ChatGPT and DeepL are increasingly used by students to assist translation, vocabulary development, and independent study activities. Knowledge Gap: However, limited empirical studies examine the intensity of AI utilization and its multidimensional consequences on students’ learning behavior in Indonesian Islamic senior high schools. Aims: This study aims to analyze the intensity of AI use and to identify its positive and negative consequences in Arabic language learning at SMA Muhammadiyah 01 Taman Sidoarjo. Results: Using a qualitative case study approach with interviews, observations, and documentation involving teachers and Grade XII students, the findings reveal high utilization of AI as a translation and learning support tool. Positive outcomes include increased learning motivation, flexible access to materials, time efficiency, and expanded Arabic vocabulary. Conversely, negative consequences involve technological dependency, reduced social interaction, decreased critical thinking initiative, technical access issues, and occasional inaccuracy in translation results. Novelty: The study highlights the dual consequences of AI utilization within a specific senior high school context, emphasizing dependency risks alongside learning benefits. Implications: The findings underline the necessity of active teacher guidance to ensure AI functions as a supportive instrument rather than a substitute for pedagogical roles. Keywords: Artificial Intelligence, Arabic Language Learning, Qualitative Case Study, Student Dependency, Secondary Education Key Findings Highlights: High classroom reliance on digital translation platforms among Grade XII learners. Motivation growth and vocabulary expansion reported during technology-assisted study. Critical thinking reduction and social interaction decline identified as emerging concerns.